PENGEMBANGAN LITERASI SENI KALIGRAFI BAGI REMAJA DI PERPUSTAKAAN MUDA BHAKTI DESA NGABLAK - Hilyah Diyan Kafita; Ahmad Majidun; Dakusta Puspitasari (khidmatan, 2024)
This Community Service (PkM) activity was conducted at Muda Bhakti Village Library, Ngablak Village, to address a literacy gap, where the penetration of foreign culture poses a risk of eroding the Nusantara Islamic cultural heritage, particularly among young children. The primary objective of the program was to develop calligraphy literacy as a form of visual art literacy, which represents the crystallization of Islamic ideology. The methodology utilized was Participatory Action Research (PAR), involving local stakeholders in the planning and implementation phases. Core interventions included calligraphy coloring training for kindergarten participants and the addition of Islamic calligraphy art book collections to strengthen the library's assets. Observation results showed significant success, with 70% of participants demonstrating good skills in the practical calligraphy coloring sessions. The program successfully broadened the function of the Muda Bhakti Library from merely a book lending center to a center for visual literacy development and local cultural preservation, asserting its contribution to fostering creativity and cultural awareness in Ngablak Village.